2016
DOI: 10.18805/ijar.10273
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chedu and mattha on growth performance of Murrah buffalo calves

Abstract: The aim of the present study was to determine the effect of chedu and mattha on growth performance of Murrah buffalo calves. To assess the effect of chedu and mattha on growth rate, 20 growing buffalo calves of around 1 year of age and approximately of same weights were selected and were divided into 4 treatment groups having 5 animals in each group. The animals had access to ad libitum berseem hay as the basal roughage T 0 (Control), T 1 (Administration of mattha @ 2% of body weight with salt @ 0.5% of mattha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
1
1
0
Order By: Relevance
“…This could be attributed to the fact that animals in T3 exhibited the most significant feed intake, resulting in an increased supply of nutrients to the body, which was then transformed into more body proteins. Regarding this matter, the serum total protein level indicates the animal's nutritional condition and is directly related to the amount of protein consumed in the meal (Kumar et al, 1980). In addition, these results align with the research carried out by Abu El-Ella and Kommonna (2013), who demonstrated that Damascus goats supplemented with 2.5g SC/head/day exhibited the most significant (P<0.05) elevation in blood total protein levels.…”
Section: Blood Serum Parameterssupporting
confidence: 86%
“…This could be attributed to the fact that animals in T3 exhibited the most significant feed intake, resulting in an increased supply of nutrients to the body, which was then transformed into more body proteins. Regarding this matter, the serum total protein level indicates the animal's nutritional condition and is directly related to the amount of protein consumed in the meal (Kumar et al, 1980). In addition, these results align with the research carried out by Abu El-Ella and Kommonna (2013), who demonstrated that Damascus goats supplemented with 2.5g SC/head/day exhibited the most significant (P<0.05) elevation in blood total protein levels.…”
Section: Blood Serum Parameterssupporting
confidence: 86%
“…To create a well-herd composition, the heifers to be included into the herd should be available for high-yield and they should be well-developed to present their potential, in other words, they should reflect these characteristics on phenotypes. Such a case can only be possible with well-nutrition and care of calves from the first day of their birth on (Kumar et al, 2017;Zhang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%